PENERAPAN VECTOR AUTO REGRESSION (VAR) PADA VARIABEL MAKRO EKONOMI DAN PASAR SAHAM DI BURSA EFEK INDONESIA - Rumbiati, Rumbiati (Jurnal Ilmu Manajemen, 2013)
Macro economy policy that goverment using to counter of destruction og global economic crisist to influence portfolio invesment activity doing buy market broker ecpecially on capital investment in capital market. Money policies taken from goverment to control worse impact from global crisis,bdgin from to increase of interest rate, to increase of fuel priced, although to control money changer activities. This paper analyzes the relationship between macro economy variable (inflation, interest rate of Indonesiancentral banking, and exchange rate) and Indonesian stock market by applied The Vector Auto Regression (VAR) method. This paper focused on three period samples of observation, pre period of global crisis covering (2008:1)to the pasca period of global crisis (2010:12). The result of Granger Causality test showing that relationship between macro economy variable and stocks market to poduce system of feedback causality, which growing ofexchange rate rupiah to US Dollars and inflation have a one row transmission. Stock index of Indonesian have influenced feedback to exchange rate. However feedback influence focusing on growing BI rate to mechanism of Indonesian stock index and influence of exchange rate to Indonesian stock index.